Evaluasi Kinerja Aparatur Sipil Negara Di Kantor Pemerintahan - Bernadi Gamal Salam; Sri Sundari; Marisi Pakpahan (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study discusses, in general, the evaluation of the work carried out by the Civil State Apparatus (ASN) in the environment of government offices in Indonesia. Enhancing the quality of ASN performance is one of the most optimal methods and strategies for improving service performance and giving recognition to specific service units that have a view to delivering optimum service and performance in the office environment. This means that the empowerment implemented against ASN can improve performance more optimally. The methods used in this research are qualitative methods, where research is carried out by collecting data and information from a variety of literary sources, such as books, journals, and other literary resources. In an age of increasingly stringent and diverse global competition, the human resources (HR) aspect has become a very essential element that plays a key role in the sustainability of a company or organization. The results of the research show that the evaluation of the work of ASN has an impact on the performance of ASN in doing its work in the company's office environment. The conclusion obtained from the results of this research is to empower the quality of ASN performance to be one of the most optimal methods and strategies in the effort to improve service performance and to give recognition to certain service units that can provide service, evaluation, and performance quite optimally in the environment of the government office.